Khazana Warna berdasarkan Alam dan Budaya Nusantara (2) - Mita Purbasari; R.A. Diah Resita I. K. Jakti (Humaniora, 2011)
More than any other element of design, color has the ability to makes us aware of what we see, for nothing has meaning without color. Color naming tries to describe color of objects surrounding us. The physiology of the eye and how light imparts color to objects, as well as the psychological and cultural factors involved in perception. These factors in turn affect whether an artist chooses to use local, optical, or arbitrary color. The color defines our world. Just like the previous paper, this research uses quantitative and qualitative methods to describe the color names and color names of the new proposed based on the audience choice. Data collected will be used as a proposal of naming colors in Indonesian language that uses the unique natural and cultural riches of Indonesia itself.